Caracterização geotécnica do perímetro urbano do município de Chapecó-SC através do geoprocessamento de sondagens SPT em ambiente SIG - Xavier, Andressa Vigne (2020)
Chapecó Municipality over the past years has been presenting population and economic growth rates even greater than the state rate. The urban perimeter has been receiving huge investments from the civil construction, with enterprises increasingly contemporary and bold. Thus, the knowledge of geotechnical characteristics of the soil of the municipality urban perimeter is essential to the steps of project, planning and development of the construction, not to mention the prevention of pathologies and foundation elements optimization. Based on this demand, the present study submits a geotechnical database structure as of the SPT analysesover the urban perimeter of Chapecó. Based on this data model, the aim was to perform a geotechnicalcharacteristics mapping of the study area. As a result of this mapping, thematicmaps were elaborated presenting characteristics as the soil map for each depth layer, the incidence of the groundwater level, SPT impenetrable layer depth and the figures of the NSPTparameter. In addition, orientation maps regarding foundation type, allowable stress of the soil and maximum length of pile of the type bored piles and continuous flight auger.For the database composition, 90 survey reports held were selected, as of 2014.Theattributesweresubmitted to geostatistics treatments in GIS environmentand were modeled with two interpolation methods assist: ordinary kriging and weighed inverse of the distance.A quality control of the generated maps from the two interpolation methods used was also accomplished, where became possible to conclude that the most representative model method was ordinary kriging. With the elaboration of the present study, it was possible to come to conclusion that the geotechnical database geo-processing will act as an important technical instrument to sustain studies, the constructions and projects planning, as well as, lead better strategies to be taken by professionals of the area to minimize suppositions with respect to the characteristics and parameters of the soil of the urban perimeter of Chapecó municipality.With the presented maps, it is possible to obtain the knowledge, even in larger scales, of the main geotechnical characteristics of the study area.